If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f + 32 = 39 Reorder the terms: 32 + f = 39 Solving 32 + f = 39 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + f = 39 + -32 Combine like terms: 32 + -32 = 0 0 + f = 39 + -32 f = 39 + -32 Combine like terms: 39 + -32 = 7 f = 7 Simplifying f = 7
| -1=4x+5 | | f+32f=29 | | -2=4x+5 | | 4x-9+2x=15 | | n+5215=24360 | | 3142/x=.06 | | 16x-6x+70-84=28-4x | | n-5215=24360 | | -cos(x)+sin(2x)=0 | | a-11a=18 | | 4=c-2 | | 7y=5x-1 | | 97=2.1p+27.7 | | 4x-2(-2)=10 | | 9xsquared+11x-14=0 | | 9.75km=m | | 7y=2-5x | | m+20=12 | | y=-1+0.8x | | 17=15y-3 | | 2x=9x+5 | | 6x+4=2(18-x) | | 9w+9=9w+9 | | 5y=4x-5 | | 4d-3=d+9 | | 6-3c=c+8 | | 3(2x+1)=5(x+3) | | (14x-13)(5x+13)=70X^2+182 | | 8-3b=4-2b | | 8k^2+10k+3=0 | | 2(10-3x)=8 | | 10x=1.8x+32 |